2016
DOI: 10.1080/17512433.2016.1200971
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of combining clozapine with electrical or magnetic brain stimulation in treatment-refractory schizophrenia

Abstract: We conducted a systematic literature search through Pubmed and cross-references for relevant publications evaluating the safety and efficacy of combining BST with clozapine. Expert commentary: Evidence from a randomized controlled trial and open-label trials suggest that ECT is an effective intervention in clozapine-refractory schizophrenia. There is limited evidence that the combination is safe. However, until sufficient data accumulate, it would be prudent to be vigilant against adverse effects related to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 62 publications
0
26
0
11
Order By: Relevance
“…The reported effects were either AEs typical of tDCS or of the medication, e.g., vertigo, tiredness, vomiting, (dopaminergics, NMDA receptor antagonists or benzodiazepines). No SAEs have been reported with combinations, e.g., tDCS and clozapine (Arumugham et al, 2016). Thus, currently there is no evidence that the combination of pharmacotherapy with TES results in enhanced risks exceeding AEs, which can attributed to the respective single interventions.…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…The reported effects were either AEs typical of tDCS or of the medication, e.g., vertigo, tiredness, vomiting, (dopaminergics, NMDA receptor antagonists or benzodiazepines). No SAEs have been reported with combinations, e.g., tDCS and clozapine (Arumugham et al, 2016). Thus, currently there is no evidence that the combination of pharmacotherapy with TES results in enhanced risks exceeding AEs, which can attributed to the respective single interventions.…”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…Indeed, in a rat seizure model, Liebetanz et al (2006) reported that seizure threshold was not reduced by anodal tDCS (Liebetanz et al, 2006). tDCS within the standard protocols is considered safe for both adults and children and for both healthy subjects and patients (Nitsche and Paulus, 2001, Nitsche and Paulus, 2015, Nitsche et al, 2003a, Nitsche et al, 2003b, Arul-Anandam et al, 2009, Borckardt et al, 2011, Borckardt et al, 2012, Peruzzotti-Jametti et al, 2013, Bennabi et al, 2015, Gillick et al, 2015, Ho et al, 2015, Krishnan et al, 2015, Matsumoto and Ugawa, 2015, Meron et al, 2015, Moliadze et al, 2015, Oberman and Enticott, 2015, San-Juan et al, 2015, Smit et al, 2015, Xu et al, 2015, AparĂ­cio et al, 2016, Arumugham et al, 2016, Bikson et al, 2016, Cha et al, 2016, Gbadeyan et al, 2016, Hu et al, 2016, Muszkat et al, 2016, Palm et al, 2016, Rubio et al, 2016, Shivakumar et al, 2016, Woods et al, 2016). Yet it remains important to be aware of the potential adverse effects of tDCS.…”
Section: Introductionmentioning
confidence: 99%
“…CSP elongation was also observed after successful treatment of schizophrenia by ECT and rTMS [22,23]. In connection with the evidence suggesting GABABneurotransmissiondeficiency in schizophrenia [24], it seems reasonable to combine these stimulation methods with clozapine in patients resistant to antipsychotic therapy [11].…”
Section: The Efficacy and Safety Of Ect In Combination With Clozapinementioning
confidence: 91%
“…It should be noted that treatment with clozapine only is sometimes associated with the risk of serious side effects (hematologic, cardiac or metabolic), which should be taken into account in choosing the appropriate method of augmentation [11]. This problem, among other things, prompts the search for non-pharmacological methods of augmentation with clozapine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation